VirtumFi: Pengembangan Bahan Ajar Terintegrasi Android dan Soal HOTS pada Topik Gejala Kuantum untuk SMA - Kurniawan, Fatah; Sulur, Sulur; Pramono, Nugroho Adi; Amiruddin, Mohd Zaidi Bin; Samsudin, Achmad; Kapıcı, Hasan Özgür; Darmawan, Alif (JPPS (Jurnal Penelitian Pendidikan Sains), 2024)
Objective:  One of the physics materials that are very important for students is quantum phenomena because it cannot be separated in everyday life.  This research aims to develop a learning media "VirtumFi: Quantum Phenomena” for high school students that is feasible and practical. Method: This research is development research that used the 4D design (Define, Design, Develop, Disseminate) in the development process. Development was carried out using Adobe Animate software as an Android application development software.  Results: VirtumFi has been tested valid in content and construct. In addition, VirtumFi is equipped with teaching materials and HOTS question instruments to evaluate student understanding related to Quantum phenomena.  Furthermore, VirtumFi is accessed using Android so that it can be used anywhere. Novelty: The novelty that can be multiplied in this research is the VirtumFi (Virtual Laboratory Fisika) product in the form of Android with a combination of teaching material (text materials and worksheets), HOTS questions, and virtual laboratories.